Ekstraordinær sendemann. Władysław Neuman, Polens minister i Norge 1931-1942 - Lange, Tadeusz Wojciech (Folia Scandinavica Posnaniensia, 2007)
The purpose of this short article is to present adjectival compositional-derivational word-formations (= samdannelser) in contemporary Danish with regard to their structure, morphology and partly their semantics. There are different interpretations of the notion “samdannelser” in Danish scholarly literature. My point of reference is Paul Diderichsen’s description of this term. This description is based on a morphological analysis. A few types of structures are presented and some morphological phenomena and changes concerning the individual examples are described.